Malaysian undergraduate ESL students' perception of blended learning - Bolandifar, Saeideh; Noordin, Nooreen; Rafik-Galea, Shameem; Mohd Ayub, Ahmad Fauzi (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The development of Information and Communication Technology (ICT) in tertiary education has encouraged many institutions to try and use new approaches in the teaching and learning process. Among these approaches, blended learning is considered a novel method of instruction which was developed not so long ago and has been used extensively over the years. The present study examined the perception of Malaysian undergraduate ESL students toward the implementation of blended learning. The participants were 21 Malaysian undergraduates in the field of TESL (Teaching English as a Second Language) in a public university in Malaysia. The integration of face-to-face instruction and computer-mediated instruction was utilized for the blended learning approach. The questionnaire on Students’ Views on Blended Learning and Its Implementation was distributed among the students. To strengthen the quantitative findings, semi-structured interviews were also conducted. Findings show that students have positive views on the implementation of blended learning. They found blended learning as a new approach which provides a comfortable learning environment for them and encourages them to be more autonomous in their learning process.